(untitled) (International Journal of Food and Nutritional Sciences, 2022)
4-Amino-2,6-dimethylpyrimidine (ADMP) is a pyrimidine derivative with promising pharmacological and industrial applications due to its versatile biological activities and electronic properties. This study provides an integrated experimental and theoretical characterization of ADMP using Fourier transform infrared (FT-IR), Raman, and UV-Vis spectroscopy, supported by density functional theory (DFT) at the B3LYP/cc-pVTZ level. Vibrational spectral analysis revealed 48 distinct vibrational modes, with excellent agreement between experimental and theoretical frequencies. UV-Vis spectral analysis highlighted π → π* transitions, confirming the molecule’s photoactive behavior. Mulliken charge distribution and molecular electrostatic potential (MEP) analyses provided insights into electronic properties, while frontier molecular orbitals (FMOs) analysis highlighted ADMP’s kinetic stability and reactivity. In vitro antibacterial studies against S. aureus, K. pneumoniae, E. coli, and P. aeruginosa confirmed broad-spectrum antimicrobial activity. Additionally, MTT assays demonstrated significant better anticancer potential against HeLa compared to A549 cell lines. The present work will be very useful for the development of potential bioactive agent in Pharmaceutical applications.